AN OBSERVATIONAL STUDY OF KNOWLEDGE, ATTITUDE AND PRACTICE OF USAGE OF ORAL CONTRACEPTIVE PILLS AMONG UNDERGRADUATE STUDENTS OF THIRD FIRST MBBS IN A TERTIARY CARE TEACHING HOSPITAL - mehta, Prachi; dudhia, sneh (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Education about contraceptive measures in reproductive health is of utmost importance. Doctors can directly influence the patients, and it is, therefore, necessary to know their attitude toward contraceptives. This study will assess the knowledge, attitude, and practice of the usage of oral contraceptive pills (OCPs) among the students of the IIIrd first MBBS. Methods: Among 125 students of the third first MBBS, a questionnaire-based observational knowledge, attitude, perception, and practice study was conducted using Google Forms, at SBKSMI&RC (Shrimati Bhikhiben Kanjibhai Shah Medical Institute and Research Centre), Sumandeep Vidyapeeth in June 2023. Results: In our study, 59.2% of participants were female and 40.8% were male. Students were of the age 20–23 years. 60.8% of students mentioned their source of information as formal education. On being asked about the different uses of OCPs, 69.6% knew about their use as contraception and 52.8% knew their use in menstrual irregularities. In case of a dose being missed, 18.4% did not know what to do whereas 28% would consult a gynecologist and 53.6% knew what to do. 41.6% of students believed that OCPs carry significant side effects. 42.4% preferred getting OCP from medical stores. For usage or prescription in the future, 52.8% preferred barrier methods whereas 24.8% chose intrauterine devices and only 19.2% opted for OCP. When inquired on reasons for not using OCPs, 31.2% opted for fear of side effects. Conclusion: The majority of the students had good knowledge, fair attitude, and fair practice toward the use of OCPs.